A Tryptophan Metabolite of the Microbiota Improves Neovascularization in Diabetic Limb Ischemia - Ma, Xiurui; Yang, Jinjing; Yang, Guanrui; Li, Lei; Hao, Xiaojun; Wang, Guoqin; An, Jian; Wang, Fei (Frontiers in Cardiovascular Medicine, 2022)
Diabetes mellitus is accompanied by a series of macrovascular and microvascular injuries. Critical limb ischemia (CLI) is the most severe manifestation of peripheral artery disease caused by diabetes mellitus and is almost incurable. Therapeutic modulation of angiogenesis holds promise for the prevention of limb ischemia in diabetic (DM) patients with peripheral artery disease (PAD). However, no small-molecule drugs are capable of promoting diabetic angiogenesis. An endogenous tryptophan metabolism, indole-3-aldehyde (3-IAld), were found to have pro-angiogenic activity in endothelial cells (ECs). Nevertheless, the role of 3-IAld in diabetic angiogenesis remains unknown. Here we found that 3-IAld ameliorated High glucose induced mitochondrial disfunction, decreasing oxidative stress and apoptosis, and thus improving neovascularization.